QSAR and drug design : new developments and applications - 藤田, 稔夫 (Pharmacochemistry Library, 1995)
Based on topics presented at the Annual Japanese (Quantitative) Structure-Activity Relationship Symposium and the Biennial China-Japan Drug Design and Development conference, the topics in this volume cover almost every procedure and subdiscipline in the SAR discipline.They are categorized in three sections. Section one includes topics illustrating newer methodologies relating to ligand-receptor, molecular graphics and receptor modelling as well as the three-dimensional (Q)SAR examples with the active analogue approach and the comparative molecular field analysis. In section 2 the hydrophobicity parameters, log P (1-octanol/water) for compound series of medicinal-chemical interest are analysed physico-organic chemically. Section 3 contains the examples based on the traditional Hansch QSAR approach.A variety of methodologies and procedures are presented in this single volume, along with their methodological philosophies.